2011
DOI: 10.1542/peds.2011-0480i
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Obesity Programs at Children's Hospitals: Insights From Senior Program Administrators

Abstract: OBJECTIVE:The obesity epidemic has resulted in an increasing number of children needing multidisciplinary obesity treatment. To meet this need, pediatric obesity programs have arisen, particularly in children's hospitals. In 2008, the National Association of Children's Hospitals and Related Institutions (NACHRI) convened FOCUS on a Fitter Future, a group drawn from NACHRI member institutions, to investigate the needs, barriers, and capacity-building in these programs. METHODS:Senior administrators of the 47 NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Multidisciplinary approaches in diverse sectors, including pediatric primary care, have been proposed to reduce the high prevalence of childhood obesity [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary approaches in diverse sectors, including pediatric primary care, have been proposed to reduce the high prevalence of childhood obesity [4]. …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Advocacy organizations such as the Children' s Hospital Association also have supported pediatric quality improvement projects executed by its members throughout the United States. [14][15][16] Over the last several years, children' s hospitals in selected states have begun to recognize the value of collaboration at a statewide level. 17,18 The partnerships that form within states have the advantages of proximity for meeting opportunities and shared state regulations for data transparency.…”
Section: Discussionmentioning
confidence: 99%
“…While RDs have been proven effective for treating patients with a variety of medical nutrition conditions, they are rarely integrated into primary care teams [88]. In addition, low reimbursement of obesity interventions and high overhead costs are of concern to hospitals administrators [89, 90]. Lee et al (2010) [91] showed that Medicaid in ten states addressed childhood nutritional and behavioral therapy reimbursement and billing codes for obesity, Medicaid in ten states did not address it, and Medicaid in the remaining 30 states had unclear guidelines.…”
Section: Review Processmentioning
confidence: 99%